2016
DOI: 10.17219/dmp/62229
|View full text |Cite
|
Sign up to set email alerts
|

Bactericidal Efficacy of Different Diode Laser Operation Modes Against Enterococcus faecalis Compared with Sodium Hypochlorite Irrigation

Abstract: Microorganisms surviving in the root canal system despite the chemomechnical preparation are the main reason for reinfection and endodontic treatment failure [1]. Among them, Enterococcus faecalis is the most commonly isolated bacterium from teeth with periapical periodontitis with or without periodontal lesions [2][3][4]. Because of its ability to form intra-and extraradicular biofilms, AbstractBackground. Microorganisms surviving in the root canal system despite the chemomechanical preparation are the main … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
(47 reference statements)
0
2
0
Order By: Relevance
“…Grącka-Mańkowska et al also investigated the bactericidal efficacy of different diode laser operation modes against Enterococcus faecalis under in vitro conditions. 30 Bovine teeth were infected with the bacterial strain and a high-power diode laser was applied with the parameters of 1.5 W CV and 3 W impulse irradiation. In both experimental groups, the mean number of bacterial cells was reduced: in 1.5 W group by 97%, and in 3 W by 93%.…”
Section: Discussionmentioning
confidence: 99%
“…Grącka-Mańkowska et al also investigated the bactericidal efficacy of different diode laser operation modes against Enterococcus faecalis under in vitro conditions. 30 Bovine teeth were infected with the bacterial strain and a high-power diode laser was applied with the parameters of 1.5 W CV and 3 W impulse irradiation. In both experimental groups, the mean number of bacterial cells was reduced: in 1.5 W group by 97%, and in 3 W by 93%.…”
Section: Discussionmentioning
confidence: 99%
“…14,[16][17][18] However, some studies have reported that merely irradiating the root canal with a diode laser reduces the bacterial load more than traditional irrigation methods. 13,[19][20][21][22][23][24][25] To achieve higher levels of disinfection, the diode laser has been used coincide with irrigation with distilled water, 26,27 ozonated water, 26 saline, 12,22 chlorhexidine, 27 silver nanoparticles, 27 and another laser application. 28 Additionally, the diode laser has been used in the LAI technique with NaOCl, 13,29,30 and most of these studies have reported that LAI is a more potent tactic to disinfect root canals.…”
Section: Diodementioning
confidence: 99%